Kānphatthanā ʻutsāhakam mai Thai nai Phāk ʻĪsān ratchasamai Phrabāt Somdet Phra Čhunlačh̜̄omklao Čhaoyūhūa, Ph̜̄o. S̜̄o. 2444-2455 - Niti Kasikōson (Samnakphim Mahāwitthayālai Thammasāt, 1998)
History of development of cottage silk industry in Northeastern Thailand during reign of Chulalongkorn, King of Siam, 1853-1912.